2014
DOI: 10.1063/1.4897169
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of magnetized nanodusty plasmas in a radio frequency-driven parallel-plate reactor

Abstract: Nanodust is produced in an rf-driven push-pull parallel-plate reactor using argon with an acetylene admixture at 5–30 Pa. A scheme for the preparation of nanodust clouds with particle radii up to 400 nm for investigations in magnetized plasmas is proposed. The confinement that keeps the nanodust of different radii inside a moderately magnetized discharge (B ≤ 500 mT) is investigated by a comparison of 2d-Langmuir probe measurements in the dust-free plasma without and with a magnetic field and by the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…At this critical radius the particles leave the plasma confinement because the ion drag force and/or the gravitational force are larger than the confining electric field force. This also causes the formation of a void, a dust-free region in the center of the plasma [15,16].…”
mentioning
confidence: 99%
“…At this critical radius the particles leave the plasma confinement because the ion drag force and/or the gravitational force are larger than the confining electric field force. This also causes the formation of a void, a dust-free region in the center of the plasma [15,16].…”
mentioning
confidence: 99%
“…As mentioned above, a region with high emission intensity in the centre of the plasma bulk was not observed during phase II. In several other studies the emission profile typical for the γ-regime has been observed [56,116,161]. The presence of this region with high emission intensity in the plasma bulk has been linked to the formation of a void inside the plasma bulk [56,105].…”
Section: Dynamics Of the Sheathmentioning
confidence: 85%
“…In the future, the list of diagnostics installed on the 'Pequod'-reactor should be extended. Especially self-excited electron resonance spectroscopy (SEERS) [189], Mie elliposmetry [122,173,174], a laser fan for light scattering [101,103,116], 132 CHAPTER 5. SUMMARY AND OUTLOOK infrared absorption spectroscopy [190,191], and near-edge x-ray absorption fine structure (NEXAFS) [123] are promising candidates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How is the dust grain charge affected by the magnetic field? However, in the majority of experiments, including those studies involving weakly magnetized plasmas (Kaw et al 2002;Vasil'ev et al 2007;Pilch et al 2008;Puttscher and Melzer 2014;Tadsen et al 2014), the dust grain charge most frequently inferred from measurements of the plasma parameters and using various charging models to estimate the value of the charge. How are the inter-dust forces modified by the magnetic field?…”
Section: Research Objectivesmentioning
confidence: 99%